2020
DOI: 10.1101/2020.07.16.20153437
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Single-Cell Omics Reveals Dyssynchrony of the Innate and Adaptive Immune System in Progressive COVID-19

Abstract: A dysregulated immune response against the SARS-CoV-2 virus plays a critical role in severe COVID-19. However, the molecular and cellular mechanisms by which the virus causes lethal immunopathology are poorly understood. Here, we utilize multi-omics single-cell analysis to probe dynamic immune responses in patients with stable or progressive manifestations of COVID-19, and assess the effects of tocilizumab, an anti-IL-6 receptor monoclonal antibody. Coordinated profiling of gene expression and cell lineage pro… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
75
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 37 publications
(82 citation statements)
references
References 107 publications
6
75
0
Order By: Relevance
“…Consistent with previous scRNAseq studies, COVID19-A samples also showed an elevated S100A score compared to A.HD (Figure 3d) 19 . Pathway enrichment on shared down-regulated genes in monocytes and neutrophils revealed a significant reduction in antigen-presentation and processing, and as in COVID-19 23 , MIS-C patients had significantly reduced HLA class II (HLA-DP, DQ, and DR) expression ( Figure 3e there was a significant enrichment in myeloid-derived proteins among the differentially expressed proteins in serum (p = 1.7x10 -12 ) (Figure 3g).…”
Section: Elevated Alarmin Expression In Myeloid Cells With Post-inflasupporting
confidence: 91%
“…Consistent with previous scRNAseq studies, COVID19-A samples also showed an elevated S100A score compared to A.HD (Figure 3d) 19 . Pathway enrichment on shared down-regulated genes in monocytes and neutrophils revealed a significant reduction in antigen-presentation and processing, and as in COVID-19 23 , MIS-C patients had significantly reduced HLA class II (HLA-DP, DQ, and DR) expression ( Figure 3e there was a significant enrichment in myeloid-derived proteins among the differentially expressed proteins in serum (p = 1.7x10 -12 ) (Figure 3g).…”
Section: Elevated Alarmin Expression In Myeloid Cells With Post-inflasupporting
confidence: 91%
“…While proof-of-principle, our classifier of severe disease shows robustness and overall value in predicting disease progression based on immune profiling and near-real-time disease monitoring. Thus, it may be valuable to inform clinical action like that proposed in chronic diseases with other high-dimensional assays [50][51][52] . Moreover, we demonstrated that a classifier with a limited number of markers retains good performance.…”
Section: Discussionmentioning
confidence: 99%
“…While this may not necessarily imply absolute changes in cell numbers, we observed good overall agreement between changes in proportions and absolute counts when comparing severe and mild disease status ( Supplementary Figure 6 and Supplementary Table 7). This highlights the importance of studies employing orthogonal modalities such as cytokine profiling 51 , single-cell RNA sequencing [52][53][54][55][56] , and their integration 57,58 . Nevertheless, even without orthogonal studies, our machine learning approach for predicting disease severity demonstrates predictive potential, although it should be tested in a validation cohort before use in a clinical setting.…”
Section: Discussionmentioning
confidence: 99%
“…ARID5A, SOCS3, PIM1, BCL3, BATF, MYC that are associated with the IL-6 pathway 56 . Cytotoxicity associated genes include PRF1, GZMH, IFNG, NKG7, KLRG1, PRF1 56 and GNLY, GZMB, GZMK 78 .…”
Section: Methodsmentioning
confidence: 99%